Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournamen (TGT) Dalam Meningkatkan Hasil Belajar PPKn - Musthofa Rizal; Siti Tiara Maulia (Shofanah Media Berkah, 2023)
This study aims to determine the effect of the Teams Games Tournament (TGT) Cooperative Learning Model in Improving PPKn Learning Outcomes for Class VIII Students of SMP Negeri 4 Merangin. This research is included in the Experimental Design research. The population of this study included all students of class VIII SMP Negeri 4 Merangin which consisted of 2 classes, two classes of the total population, namely VIII F (Experimental Class) and VIII D (Control Class) as research samples. The test instrument in this study was in the form of practice questions. Based on the results of the study, the data obtained in the normality and homogeneity tests were also normally distributed and homogeneous, then in the paired sample test it was found that the sig (2 tailed) value was 0.00 or less than 0.05 (0.00 <0.05). Significance of the use of the Teams Games Tournament (TGT) learning model for the learning outcomes of Civics subjects in class VIII students of SMP Negeri 4 Merangin. So it can be said that Ha is accepted and Ho is rejected, namely the final result is that there is an influence of the Teams Games Tournament (TGT) learning model on learning outcomes in PPKn subjects for class VIII students of SMP Negeri 4 Merangin.